Perencanaan Tata Kelola Air Pasang Surut Permukiman Penduduk Desa Kenten Laut Kabupaten Banyuasin - Pratama, M. Ade Surya; Sari, Anggi Nidya; Sakri, Harfa; Yurnalis, Fido (Jurnal Talenta Sipil, 2024)
Humans have utilized tidal events at river mouths for a long time. The major benefit is the use of raw water for domestic water needs. On an average day, there will be one high tide and one low tide with a single diurnal tidal type. The utilization of surface water during tides in the Talang Kelapa sub-district of Banyuasin Regency is not optimally used, where there is a lack of adequate water sources. In addition, there has been no research on tidal water management systems in the study area. This study aims to analyze the availability of raw water, analyze the need for raw water for the daily needs of the community, evaluation a raw water system in the residential area of Kenten Laut Village so that during the dry season the need for raw water for residential households can be met. The results of the evaluation of the availability of raw water that can be utilized from the available channels (types 1, 2, 3, and 4) are 1.17 liters/second. The results of the calculation of the mainstay discharge of 1.703 liters/second with a total amount of water availability of 2.87 liters/second. While the total domestic and non-domestic water needs. While the total domestic and non-domestic water demand based on the population in 2022 is 12.99 liters/second. It can be concluded that the availability of tidal water in Kenten Laut Village has not been able to meet household water needs so alternatives are needed, namely water reservoirs, repairing damaged drainage channels, or repairing damaged drainage channels.